The Influence of Public Relations and Customer Value Marketing on Customer Loyalty in Janji Jiwa Poris - Muhamad Fikri Sani; Sri Vandayuli Riorini (Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to examine public relations, customer value marketing and customer loyalty. The sampling technique used was purposive sampling, i.e. people who had bought the product of the promise of soul in Poris with a total of 125 respondents. The data used was by distributing Google forms. Hypothesis testing using the simultaneous test method (F test) and the coefficient of determination test (R²). The test results prove that public relations and customer value marketing have a positive effect on customer loyalty.